Collaboration Between Guidance and Counseling Teachers and Guardian Teachers in Improving the Academic Achievement of Vocational School Students - Larasati, Nariswari Dian; Nurila, Novia Manza; Lelo, Yohana Ayu Putri; Setiyowati, Arbin Janu; Ratnasari, Intan; Saputra, Nur Mega Aris (Universitas Negeri Malang, 2024)
Efforts to improve student academic achievement are not only the responsibility of the student but also require the role of guardian teachers and guidance and counseling teachers at school as supporters of successful student achievement. This research aims to determine the form of collaboration between guardian teachers and guidance counselors in improving student academic achievement. This research design uses a qualitative-descriptive research method with the subjects being guidance counselors, guardian teachers and students. The data collection instrument used interviews and was analyzed descriptively. Research findings show that there is effective collaboration between guidance and counseling teachers and guardian teachers in improving student academic achievement. It is hoped that the results of this research can be a reference for guidance and counseling teachers and guardian teachers in improving students' academic achievement, especially in vocational schools.